ANALISIS NILAI BUDAYA DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA - Alamsyah, Nur; Hayati, Nur; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study aims to reveal and analyze the cultural values contained in the novel Tenggelamnya Kapal Van der Wijck by Hamka. This research employs a qualitative approach with a descriptive-analytical method to examine the representation of Minangkabau culture in the story. The results of the study conclude that the novel is rich in cultural values, especially those of Minangkabau, and highlights the conflict between traditional and modern values. The Minangkabau society is depicted as deeply rooted in customs, including a matrilineal kinship system and a strong family role in matchmaking. Cultural values influence social values, as reflected in the strong social hierarchy between the aristocracy ("blue-blooded" nobles) and common people. Social conflict between social status values and personal values (such as love, education, and morality) becomes the central theme. The love between Zainuddin and Hayati is tested by cultural pressures but remains emotionally eternal as a reflection of loyalty, sacrifice, and true love despite their separation. The novel emphasizes the importance of justice, modesty, and valuing individuals based on character rather than lineage or wealth. It strongly criticizes social inequality rooted in unjust cultural norms, while highlighting noble values such as education, loyalty, and morality. Tenggelamnya Kapal Van der Wijck is a reflection of the struggle between tradition and human conscience.